2012
DOI: 10.3233/jad-2012-120124
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Enzymatic Activities in Alzheimer's Disease: The Relationship to Acetylcholinesterase Inhibitors

Abstract: The mode of action of acetylcholinesterase inhibitors (AChEIs) in Alzheimer's disease (AD) is mainly by potentiating neuronal transmission. Animal studies have also consistently described a role for AChEIs in enhancement of antioxidants and attenuation of oxidative stress. The influence of AChEIs on blood antioxidants in AD patients has not been established before. Furthermore, AChEI treatment, or lack of it, may have contributed to the inconsistent antioxidant data reported by other studies so far. Here we so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 38 publications
0
22
0
1
Order By: Relevance
“…However, human studies in AD patients have not yet supported these findings; AChEI treatment was found to have no effect upon blood anti-oxidant (Klugman et al 2012) or pro-inflammatory biomarker levels after one year of treatment (Richardson et al 2013). …”
Section: Effect Of Treatmentmentioning
confidence: 91%
“…However, human studies in AD patients have not yet supported these findings; AChEI treatment was found to have no effect upon blood anti-oxidant (Klugman et al 2012) or pro-inflammatory biomarker levels after one year of treatment (Richardson et al 2013). …”
Section: Effect Of Treatmentmentioning
confidence: 91%
“…Thus, the cholinergic transmission also plays an important role in modulating the phosphatidylinositol signals and extracellular regulated kinase pathways in adult neurogenesis [55]. Klugman et al also suggested that AChEIs reduce oxidative stress and mitochondrial dysfunction in AD [56]. …”
Section: Neurotransmitter-based Therapeutics In Admentioning
confidence: 99%
“…Indeed, recent data suggested that AChEIs might act directly on oxidative stress by enhancing antioxidant activity. 13 Thus, imbalances in oxidative stress/antioxidant activities may reduce the overall response to AChEIs by two ways. First of all, they may reduce the overall health of cholinergic neurons, 35 , 36 thus limiting their capability to respond to the nervous signal.…”
Section: Discussionmentioning
confidence: 99%
“… 11 , 12 Recent data suggested that AChEIs may act directly on this process, enhancing antioxidant activity and attenuating oxidative stress. 13 …”
Section: Introductionmentioning
confidence: 99%